The effect of intracerebroventricular injection of histamine in visceral nociception induced by acetic acid in rats - Zanboori, Ali (Medknow Publications, 2010)
OBJECTIVE: This study was designed to investigate the role of brain histamine and H1 and H2 receptors in mediating the central perception of visceral pain in rats. MATERIALS AND METHODS: In conscious rats implanted with a lateral brain ventricle cannula, the effect of intracerebroventricular (i.c.v.) injection of histamine (2.5, 10, and 40 μg), and chlorpheniramine and ranitidine at the same doses of 5, 20, and 80 μg were investigated on visceral pain. Visceral nociception induced by intraperitoneal (i.p.) injection of acetic acid (1 mL, 1%), and the number of complete abdominal wall muscle contractions accompanied with stretching of hind limbs (writhes) were counted for 1 h. RESULTS: Histamine at doses of 10 and 40 μg and chlorpheniramine and ranitidine at the same doses of 20 and 80 μg, significantly decreased the numbers of writhes (P < 0.05). Pretreatment with chlorpheniramine and ranitidine at the same dose of 80 μg, significantly prevented histamine (40 μg)-induced antinociception (P < 0.05). CONCLUSION: The results of this study suggest that brain histamine may be involved in modulation of visceral antinociception through both central H(1)and H(2)receptors.